2012
DOI: 10.1002/kin.20573
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependence of the bimolecular channels of the ClO + ClO reaction over the range T = 298–323 K

Abstract: The bimolecular channels of the ClO self-reaction, although negligible under stratospheric conditions, become significant above ambient temperature. The kinetics of two of the three bimolecular channels of the ClO self-reaction, ClO + ClO → Cl 2 + O 2 (1b) and ClO + ClO → OClO + Cl (1d), were studied at T = 298-323 K and at ambient pressure ( p atm ≈ 760 ± 10 Torr). Radicals were generated via laser photolysis and monitored using UV absorption spectroscopy. The inclusion of charge-coupled device (CCD) detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A suitable reference spectrum of ClO is then analogously filtered and the filtered spectrum fitted to the experimental spectrum, minimising the sum of squares of residuals to determine the ClO species concentration using the Beer Lambert law (ii), and also as described in detail previously. 22 , 23 In this way, the ClO concentration as a function of time was unequivocally extracted from the time resolved spectra recorded on the CCD, despite the presence of many other absorbing species in the spectral window studied.…”
Section: (Iv) Determination Of Clo Concentrationsmentioning
confidence: 99%
“…A suitable reference spectrum of ClO is then analogously filtered and the filtered spectrum fitted to the experimental spectrum, minimising the sum of squares of residuals to determine the ClO species concentration using the Beer Lambert law (ii), and also as described in detail previously. 22 , 23 In this way, the ClO concentration as a function of time was unequivocally extracted from the time resolved spectra recorded on the CCD, despite the presence of many other absorbing species in the spectral window studied.…”
Section: (Iv) Determination Of Clo Concentrationsmentioning
confidence: 99%
“…As discussed previously, 22 uncertainty in s ClO was defined at the 2s level from three values of the ClO cross-sections measured at T = 298 K. This gave rise to a relative error in s ClO of 0.23 at T = 298 K, of 0.26 at T = 314 K and of 0.15 at T = 246 K. This temperature dependence of the relative errors reflected the uncertainties in the high-resolution differential ClO crosssections derived by Boakes et al and employed in the current work to obtain s ClO at the resolution of the current study. The errors in the ClO cross-section were propagated through the analytical procedure and the values of k 1 and k 1c resulting from perturbed cross-sections were within AE12% and AE28% of those obtained using unperturbed cross-sections at T = 314 K. Similarly, at T = 246 K, values of k 1 and k 1c were within AE8% and AE13% of those obtained using unperturbed cross-sections.…”
Section: Sensitivity Analysismentioning
confidence: 66%
“…This was consistent with FACSIMILE simulations, showing that (as expected) OClO production via one of the bimolecular channels of the ClO self-reaction would be too slow to be appreciable over the timescales used. 22 It was therefore concluded that the mechanism forming OClO in the precursor mixture, although unidentified, did not significantly affect the [OClO] temporal trace.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations